Durability and mechanical behavior of CFRP/Al structural joints in accelerated cyclic corrosion environments. (October 2020) - Chen, Yiwei; Li, Maojun; Yang, Xujing; Wei, Kai
Abstract: This study aims to evaluate detailed corrosion characteristics and mechanical performance of CFRP/Al bonded and hybrid bonded-riveted joints subjected to cyclic salt mist-dry-wet environments. Results indicated that joint strength of both bonded and hybrid joints progressively declined with increased ageing cycles with up to 40.4% and 31.9% degradation, respectively. Compared with purely bonded joints, hybrid joints presented superior mechanical properties and less degradation rate. Light fiber tearing failure and cohesive failure predominated for less aged joints, while more apparent interface failure and accumulated corrosion products were observed at higher ageing cycles. The main corrosion mechanism was the pitting corrosion on the aluminum substrate surface, which further led to the formation of accumulated corrosion products and disbonding of the aluminum/adhesive interface. Rivet body of hybrid joints remained pristine and rivet heads experienced severe galvanic corrosion, while these corrosion features generated limited impact on joint performance.